2021
DOI: 10.1007/978-3-030-69488-3
|View full text |Cite
|
Sign up to set email alerts
|

Place-Name Politics in Multilingual Areas

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The current sociolinguistic context witnesses the presence of autonomous territoriality in which, in addition to Spanish and Basque, other languages of very different cultural origins coexist [73]. The political and identity issues related to multilingualism in place names have been studied by Jordan et al [74] and Mácha et al [7]. Moreover, the study of European policies and legislation is discussed by Ruiz Vieytez [75].…”
Section: On Multilingualismmentioning
confidence: 99%
“…The current sociolinguistic context witnesses the presence of autonomous territoriality in which, in addition to Spanish and Basque, other languages of very different cultural origins coexist [73]. The political and identity issues related to multilingualism in place names have been studied by Jordan et al [74] and Mácha et al [7]. Moreover, the study of European policies and legislation is discussed by Ruiz Vieytez [75].…”
Section: On Multilingualismmentioning
confidence: 99%
“…Moreover, the inherent power-relations in heritagisation may not only be apparent in what is displayed but also in how names are displayed. The font and style of letters, the accuracy of spelling, the visibility of minority language inscriptions and the hierarchy of languages all carry information about their relative importance and the local power relations of various language-speaking groups (Jordan et al 2021;Plautz et al 2021).…”
Section: Heritage As Object Of Toponymic Politicsmentioning
confidence: 99%
“…Our field experience confirmed that in comparison to the previous period, the trilingual information boards improved the visibility of the Hungarian language. Nevertheless, using the same, smaller font size for Hungarian and English might dilute the local presence of Hungarian language (see Duchêne 2012) in the same vein illustrating the inherent power relations between local majority and minority (see Jordan et al 2021;Plautz et al 2021).…”
Section: Oradeamentioning
confidence: 99%